STRATEGI LAYANAN BIMBINGAN KARIER: PERSPEKTIF KARIER DITINJAU DARI PERKEMBANGAN SISWA PADA JENJANG SEKOLAH DASAR - Suherman, Maya Masyita; Siddik, Riesa Rismawati (Quanta : Jurnal Kajian Bimbingan dan Konseling dalam Pendidikan, 2022)
Career is a lifelong process, so it needs to be formed as early as possible to achieve a career that suits the individual. Career education can be started when the child is in elementary school. At this level, children begin to be introduced to jobs in the surrounding environment. In addition, teachers, parents and the community participate in providing learning about themselves to children related to gender, morals, social skills, Self-Esteem, and Self-Efficacy. The formation of one's career must start early, so that since elementary school a child must be given an understanding of career. The understanding given can be through games by introducing jobs that exist in the environment around the home and school. Career development for children also needs to be adjusted to their developmental tasks. as parents and teachers must also know the talents and interests of children from an early age to be able to better direct children. The directives carried out here are not coercion in accordance with the wishes of the parents/teachers, but according to the potential of the child.Keywords: service strategy, career guidance, elementary school